Fruits of the city: The nature, nurture and future of urban foraging. Issue 1 (14th January 2023) - Sardeshpande, Mallika; Shackleton, Charlie
Abstract: Urban foraging is a global informal phenomenon which has been investigated in the Global North more than other parts of the world. Characterising the nature of urban foraging in the Global South is imperative given the rapid urbanisation and sustainable development priorities in the region. In this study, we interviewed 80 urban foragers in four cities in the eastern coastal region of South Africa, with an aim to understand the nature of urban foraging in a developing nation context. We asked foragers about their initiation to and motivations for foraging, their logistics, yields and associated activities, descriptions of their foraging grounds, and if and how they had changed, and what they envisage as an ideal future for foraging. Many foragers started foraging in their childhood, in the company of friends and family, and, as in the Global North, regarded it as a cultural and recreational activity. Foraging was mostly done within a 5‐km radius of home, on a weekly or fortnightly basis, and very few foragers processed or sold their foraged products. Unlike the Global North, formal green spaces were not foraged in, and were perceived to be poorly provisioned in urban planning. Forests and roadsides were equally used by the foragers, and very few had been discouraged from foraging. Most foragers were enthusiastic about the possibility of more people foraging, having designated spaces for foraging, and foraging‐based businesses such as processed products and ecotourism. We recommend that policymakers and land managers recognise and encourage foraging as a potentially sustainable use for stewardship of urban green spaces. To this end, we list the main wild edible fruit species used by foragers in the area, which could be planted in public spaces. We also suggest harnessing foragers' knowledge of useful species and spaces to develop green spaces and foraging‐based supply chains. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.